Rhesus Cytomegalovirus-encoded Fcγ-binding glycoproteins facilitate viral evasion from IgG-mediated humoral immunity - Claire E. Otero; Sophia Petkova; Martin Ebermann; Husam Taher; Nessy John; Katja Hoffmann; Angel Davalos; Matilda J. Moström; Roxanne M. Gilbride; Courtney R. Papen; Aaron Barber-Axthelm; Elizabeth A. Scheef; et al. (Nature Communications)
Abstract Human cytomegalovirus (HCMV) encodes four viral Fc-gamma receptors (vFcγRs) that counteract antibody-mediated activation in vitro, but their role in infection and pathogenesis is unknown. To examine their in vivo function in an animal model evolutionarily closely related to humans, we identified and characterized Rh05, Rh152/151 and Rh173 as the complete set of vFcγRs encoded by rhesus CMV (RhCMV). Each one of these proteins displays functional similarities to their prospective HCMV orthologs with respect to antagonizing host FcγR activation in vitro. When RhCMV-naïve male rhesus macaques were infected with vFcγR-deleted RhCMV, peak plasma DNAemia levels and anti-RhCMV antibody responses were comparable to wildtype infections of both male and female animals. However, the duration of plasma DNAemia was significantly shortened in immunocompetent, but not in CD4 + T cell-depleted animals. Since vFcγRs were not required for superinfection of rhesus macaques, we conclude that these proteins can prolong lytic replication during primary infection by evading virus-specific adaptive immune responses, particularly antibodies.